Experimental and numerical investigation of double lap adhesively bonded joints composed of KFRP and SDRP subjected to compressive loads - Adole Michael Adole; Iorwuese Anum; Umar Abdullahi; Namala Amuga Keftin (Discover Civil Engineering)
Abstract Natural fiber-based polymeric composites are widely used in a wide range of engineering applications, therefore a complete understanding of the behavior of these materials' adhesively bonded joints is required to ensure their efficiency, safety, and dependability. The single lap joint has garnered a lot of attention, but the double lap joint arrangement has received very little attention. This study aims to look into the bond performance of Kenaf Fiber Reinforced Polymer (KFRP) and Sawdust Reinforced Polymer (SDRP) utilizing the Double Lap Joint (DLJ) arrangement. To accomplish this, the kenaf fiber-polyester adherend was manufactured in a unidirectional pattern with a fiber weight fraction of 40%, while the sawdust-polyester adherend was made in a random pattern with a fiber weight fraction of 20%. The DLS joints were made with various joint geometrics, polyester adhesive as the bond material, and direct vertical compression load was applied. Finite element modelling was used to check and validate the laboratory data. It was discovered that increasing the lap length improves the load support capability of the adhesive joints while decreasing joint shear strength. The finite element results were consistent with the laboratory data, and the utilization of KFRP and SDRP in bonded adhesive assemblies showed promise for structural applications.